Performance of low rise concealed truss composite shear walls with external columns - Zhang, Dan (Array, 2018)
A review on the previous studies shows that limited analytical or experimental studies on the low-rise concealed truss shear walls with external columns under monotonic loading have already been conducted. The combination of concealed truss was welded to I-shaped steel frame and flat steel support. Two different aspect ratio composite shear walls were tested under static monotonic loading, and the failure mode, bearing capacity, ductility and stiffness were explored. A finite element model was developed and used to simulate the composite shear walls under constant axial load and lateral loading. The comparison of test results confirmed that the finite element model could predict the behavior of composite shear walls accurately. Meanwhile, stress analyses of the specimens were studied to simulate stress distribution of reinforcement, and to analyze the steel of composite shear wall with external columns at different loading stages. Taken together, this study could be a basis for developing an accurately simplified model.